Effects of aqueous leaf extracts of Azadirachta indica A. Juss. (neem) and Melia azedarach L. (Santa Barbara or cinnamon) on the intracellular development of Toxoplasma gondii Efeito de extrato aquoso de folhas de Azadirachta indica A. Juss. (nim) e Melia azedarach L. (canela ou Santa Bárbara) sobre o desenvolvimento intracelular de Toxoplasma gondii - E.J.T Melo; K.J Vilela; C.S Carvalho (Universidade Estadual Paulista, 2011)
Melia azedarach (cinnamon) and Azadirachta indica (neem) have a variety of biologically active ingredients against virus, bacteria and protozoan parasites; however, little is known about their action on Toxoplasma gondii intracellular development. Toxoplasma gondii infects all eukaryotic cells, where it establishes and multiplies inside a modified vacuole called the parasitophorous vacuole until the cell ruptures, re-infecting other cells and establishing the infection. There are no efficient chemotherapies for the elimination of T. gondii, minimizing side effects. In this study, we performed in vitro assays with neem and cinnamon aqueous extracts against the intracellular development of T. gondii tachyzoites. After treatment with neem and cinnamon for 24 h, the percentage of infected cells and the number of intracellular parasites drastically decreased. This effect was concentration-dependent. During the incubation of the extracts, progressive morphological and ultrastructure alterations led to intense vesiculation and complete elimination of the parasite from the intracellular medium. However, during the treatment with extracts, no morphological effects were observed in the structure of the host cell. These results suggest that the aqueous extracts of neem and cinnamon were capable of interfering with and eliminating the intracellular development of Toxoplasma gondii. Melia azedarach (canela) e Azadirachta indica (nim) apresenta grande variedade de ingredientes biologicamente ativos contra vírus, bactérias e protozoários, mas nenhum efeito sobre o desenvolvimento intracelular do Toxoplasma gondii é conhecido. Toxoplasma gondii infecta todos os tipos de células Eucarióticas, onde se estabelece no meio intracelular em vacúolo modificado conhecido como vacúolo parasitóforo. Neste vacúolo ocorre a replicação levando a ruptura da célula hospedeira e reinfecção de novas células, perpetuando a infecção. A quimioterapia utilizada não é capaz de eliminar o parasita além de induzir fortes efeitos colaterais. Neste estudo, nós demonstramos o efeito in vitro de extratos aquosos da canela e nim sobre o desenvolvimento intracelular do taquizoíto do Toxoplasma gondii. Após tratamento de nim e canela por 24 h, a porcentagem de infecção e o número de taquizoítos intracelulares decaiu drasticamente. Este efeito foi concentração-dependente. Durante incubação dos extratos, uma progressiva desorganização morfológica e ultraestrutural levaram a formação de intensa vesiculação e completa destruição do parasita, que passou a uma estrutura amorfa, antes da completa eliminação do meio intracelular. No entanto durante o tratamento com os extratos, efeitos morfológicos não foram observados nas estruturas da célula hospedeira. Estes resultados sugerem que os extratos aquosos de nim e canela foram capazes de interferir e eliminar o desenvolvimento intracelular do Toxoplasma gondii.